Environmental injustice and post-colonial environmentalism: Opencast coal mining, landscape and place. (January 2017) - Milbourne, Paul; Mason, Kelvin
In this article we use a case study of opencast coal mining in the southern valleys of Wales to explore the ordinary and everyday spatialities of environmental injustice. Responding to recent geographical critiques of environmental justice research and engaging with post-colonial studies of landscape and environment, we provide an account of environmental injustice that emphasises competing geographical imaginaries of landscape and 'ordinary political injustices' within everyday spaces. We begin with a discussion of how historical environmental injustices in Wales have been framed within nationalist politics as a form of colonial exploitation of the country's natural resources. We then make use of materials from recent research on opencast mining in South Wales to examine local understandings of and everyday encounters with mining, highlighting contradictory discourses of opencast mining, landscape and place, and the injustices associated with mining developments in this region.